Hyperelastic and viscoelastic characterization and modelling of silicone rubber - Malatsi, Kamogelo Desire (Stellenbosch : Stellenbosch University, 2025)
Malatsi, K. D. 2025. Hyperelastic and Viscoelastic Characterization and Modelling of Silicone Rubber. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/d45f7696-5eea-44b5-91ce-ac764113ca41